Allergic bronchopulmonary aspergillosis is associated with pet ownership in cystic fibrosis. Issue 6 (1st June 2016) - Thronicke, Anja; Heger, Nikola; Antweiler, Elisabeth; Krannich, Alexander; Roehmel, Jobst; Brandt, Claudia; Staab, Doris; Tintelnot, Kathrin; Schwarz, Carsten
Abstract: Background: Late diagnosis of allergic bronchopulmonary aspergillosis (ABPA) is associated with significant lung function decline and morbidity in cystic fibrosis (CF). The association of ABPA and domestic pet ownership in patients with CF has not been elucidated yet. Our objective was to determine the association of ABPA with pet ownership in patients with CF. Methods: Clinical and microbiological data from certified local patient registry were analyzed for 109 patients with CF aged 1–64 years: 55 pet owner and 54 non‐pet owners. The primary outcome of the retrospective observational study was the occurrence of ABPA in pet owners and non‐pet owners with CF. The free statistical software R was utilized to investigate logistic regression models for association factors. Results: Of the 109 patients included in the study, 61 (56%) were female. The mean age of the total group was 25.4 ± 13.2 years. Adjusted analysis revealed that ABPA (OR 5.0227, 95% CI: 1.182–21.340, p = 0.029) was associated with pet ownership in patients with CF. Furthermore, ABPA in pet owners with CF was associated with an increased number of exacerbations (OR 6.446, 95% CI: 1.057–39.328, p = 0.043). Other outcomes did not significantly differ. Conclusion: Owning a pet was associated with ABPA in patients with CF. Future prospective multicenter longitudinal studies are needed to investigate chronological causality between pet ownership, ABPA development, and pulmonary exacerbations and to determine whether these estimates are generalizable for ABPA susceptible patients beyond CF (asthma, bronchiectasis). Abstract :